Study on deformation characteristics and crack extension law of cement stabilized phosphogypsum materials under dry and wet cycles - Liangchun Xu; Kaisheng Chen; Yuang Chen; Hao Jian (PLoS ONE, 2025)
The resource utilization of phosphogypsum has been a worldwide problem. Previous research was limited to mixing phosphogypsum with other materials (lime, gravel, red clay) to play an auxiliary role rather than being the main part, the utilization rate is low. This study aims to assess the deformation and crack behavior of cement-stabilized phosphogypsum under varying environmental conditions, and provide theoretical basis for the application of cement-stabilized phosphogypsum materials in road engineering. The test results showed that, firstly, the absolute expansion and absolute shrinkage of cement-stabilized phosphogypsum materials increased with the increase of compaction, cement dosage and the number of wet and dry cycles, and decreased with the increase of initial water content and the dosage of phosphogypsum; Secondly, the fracture rate of cement-stabilized phosphogypsum materials increased with cement dosage and the number of wet and dry cycles; and decreased with compaction, initial moisture content, and phosphogypsum dosage; Thirdly, the relationship between the absolute expansion or shrinkage of cement-stabilized phosphogypsum materials and the compaction degree and the fracture rate is not a simple linear relationship, but is affected by a combination of factors, showing nonlinear characteristics, which can be fitted by the nonlinear binary quadratic equation f(x,y) =ax2+bx+cy2+dy+e. The compaction degree and the fracture rate are the key factors influencing the material’s volume change, while the absolute expansion or shrinkage is a quantitative indicator of the volume change of the material under specific environmental conditions. Fitting by a nonlinear quadratic equation can effectively capture the complex nonlinear relationship between the variables and provide more accurate fitting results, and by analyzing the extreme points of this equation, the optimal degree of compaction can be determined to maximize the material properties.